Socio-Economic Factors Affecting to Juvenile Delinquency:A Study Conducted at Borstal Jails of Punjab - Javed, Mudassar; Azhar, Zarqa; Anwar, Haq Nawaz; Sohail, Malik Muhammad (Asian Journal of Empirical Research, 2012)
This study aims to explore the socio-economic factors effecting juvenile delinquency. The research was conducted at Faisalabad and Bahawalpur Borstal jails of Punjab. The main objectives of the study were to find out the background characteristics of the Juveniles, to explore social factors that influence on juvenile delinquency and to identify the economic factors that influence on juvenile delinquency. Quantitative approach was used to find out appropriate results and simple random sampling was used to collect data. Sample size of 140 respondents had been taken through simple random sampling. It was concluded in the present study that peers’ negative influence, low income of family, family conflict, revenge, low literacy level and lack of parent supervision of their children were the main case of juvenile delinquency.